Strategi Peningkatan Penerimaan Situs Petra Christian University Library Dengan Menggunakan Metode Desain Web UXPin Pada Universitas Kristen Petra Surabaya - Prasetio, Max; wati, Sulistio; Rahmawati, Endra (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2018)
The site of petra christian university library started designed and built at 3 June 1995 and it have twelve online services that are still operating until now. Based on the data from Alexa provide that the site of petra christian university library has successfully reach the rank to 945 in Indonesia but the site also ever got lower ratings in September 2017. In order to reduce the risk of downgrading that could have a negative impact of changing the user point of view of the site becomes worse, then in this study conducted the analysis of Petra Christian University Library's website acceptance to students of Petra Christian University Surabaya by using the Technology Acceptance Model 2 (TAM 2) to generate recommendations that will then be modeled by a new user interface that refers to UXPin's web design method to improve the look and quality of the web.The results of Petra Christian University Library's acceptance analysis using Technology Acceptance Model 2 (TAM 2) found that the deficiencies contained in the site are poor site navigation, unsaved feedback form from users and some technical issues. UXPin's web design method is used to generate an improved Petra Christian University Library website acceptance strategy by improving the site navigation, adding a database for storing user feedback and fixing some technical issues.